Quantum probability and applications II: proceedings of a workshop held in Heidelberg, West Germany, October 1-5, 1984 - Accardi, Luigi 1947-; Waldenfels, Wilhelm von (Lecture notes in mathematics, 1985)
On the polaron asymptotics at finite coupling constant -- Stochastic calculus on local algebras -- Trapping in stochastic mechanics and applications to covers of clouds and radiation belts -- A remark on dynamical semigroups in terms of diffusion processes -- Quasi-free stochastic evolutions -- Dilations of operation valued stochastic processes -- The Doob-Meyer decomposition for the square of Itô-Clifford L2-martingales -- Poisson processes and quantum field theory: A model -- The entropy of quantum Markov states -- Entropic uncertainty relations in quantum mechanics -- Estimates of quantum deviations from classical mechanics using large deviation results -- Adiabatic elimination technique for quantum dissipative systems -- Limitations for chaotic motion in quantum mechanics -- Non commutative Lp spaces and K.M.S. functions -- Normal product states and nuclearity: New aspects of algebraic quantum field theory -- The low density limit for N-level systems -- The C?-Algebras of the two-dimensional ising model -- Infinite divisibility and central limit theorems for completely positive mappings -- Temperature-dependent lamb shift of a quantum oscillator -- Construction of stationary quantum markov processes through quantum stochastic calculus -- A model for a unified quantum description of macroscopic and microscopic systems -- Conditional expectations in Lp-spaces over von neumann algebras -- Quantum gibbs states and the zeroth law of thermodynamics -- Dissipative quantum tunneling -- Carlen processes: A new class of diffusions with singular drifts -- Adiabatic drag and initial slips for random processes with slow and fast variables -- Uses of non-Fock quantum Brownian motion and a quantum martingale representation theorem -- Supersymmetry and a two-dimensional reduction in random phenomena -- On the structure of markov dilations on W?-algebras -- A new construction of unitary dilations : Singular coupling to white noise -- A new approach to quantum ergodicity and chaos -- Quantum Markov processes on Fock space described by integral kernels -- Quantization of brownian motion processes in potential fields -- Gleason measures and quantum comparative probability -- State change and entropies in quantum dynamical systems -- Some remarks on the integration of Schrödinger equation using the quantum stochastic calculus -- Convergence almost everywhere in W*- algebras -- Properties of quantum entropy -- Semiclassical description of n-level systems interacting with radiation fields -- The charge class of the vacuum state in a free massless dirac field theory -- Derivation of classical hydrodynamics of a quantum coulomb system -- Positive and conditionally positive linear functionals on coalgebras -- The Ito-Clifford integral part II -- Detailed balance and equilibrium -- Spontaneous light emission described by a quantum stochastic differential equation.